Influential Factors Responsible for Profitability: A Technical Study on Commercial Banks in Bangladesh - Akber, S. M. (International Journal of Accounting & Finance Review, 2019)
This paper explores how many internal and external factors from 2007-2017 affect the competitiveness of commercial banks in Bangladesh. Many bank-specific variables are used to achieve the goals as internal factors, and macroeconomic variables are used as external factors. A sample of seven commercial banks will be used for this purpose. Return on equity is used as a proxy for profitability and capital adequacy, the size of asset quality banks, investment control, liquidity, resource structure, and economic indicators are used as proxies for the independent variable. The paper’s overview findings show that asset structure, capital adequacy, and asset quality are the key factors in Bangladesh’s profitability for the commercial bank. The paper’s outcome indicates that if commercial banks are more worried about these factors, they could produce a better return on the competitive market.